Health on equal terms? - Västra Götaland, 2004 - Health on equal terms, Västra Götaland - 2004 - Public Health Agency of Sweden (Region Västra Götaland, 2015)
The survey “Health on equal terms?” is a national survey, conducted every year since 2004. The Public Health Agency is responsible for the survey and Statistics Sweden (SCB) is responsible for the distribution, collection and registration. During the data collection in 2004, Region Västra Götaland ordered an additional sample for Västra Götaland County.

The additional sample in 2004 included all individuals aged 18-84 years living in Ale, Kungälv, Tjörn, Öckerö, Härryda, Mölndal, Partille and Gothenburg. The questionnaire were answered by 3,923 individuals from the additional sample.

Including the national sample produced by Statistics Sweden (SCB), a total of 5,047 individuals participated from Västra Götaland County.

The questionnaire consisted a total of 143 questions covering e.g. issues of health, lifestyle, economic conditions, work and employment, and security and social relations. In addition to data collected through the questionnaires, registry data were also included.

Purpose:

The aim of the national survey was to investigate the health in the population and to show changes in the population's health over time as a follow up of the national health politics. The aim of the additional sample in Västra Götaland County was to investigate the health in the population in Västra Götaland County.

Undersökningen ”Hälsa på lika villkor?” är en stor nationell undersökning som genomförts varje år sedan 2004. Folkhälsomyndigheten ansvarar för undersökningen medan Statistiska centralbyrån (SCB) ansvarar för utskick, insamling och registrering av svar. I samband med undersökningen 2004 beställde Västra Götalandsregionen ett tilläggsurval för Västra Götalands län.

Tilläggsurvalet för 2004 års undersökning inkluderade samtliga invånare 18-84 år som var bosatta kommunerna Ale, Kungälv, Tjörn, Öckerö, Härryda, Mölndal, Partille samt Göteborg. Frågeformuläret besvarades av totalt 5047 individer inom Västra Götalands län, varav 3923 ingick i tilläggsurvalet.

Blanketten bestod av 86 numrerade frågor, flera av dem hade delfrågor vilket genererade totalt 143 frågor. Frågorna handlade bl a om hälsa, vårdutnyttjande, levnadsvanor, ekonomiska förhållanden, arbete och sysselsättning. Förutom variabler som samlats in via frågeblanketten har ett antal registervariabler hämtats från SCB:s register över totalbefolkningen (RTB), utbildningsregistret och inkomst- och taxeringsregistret.

Syfte:

Syftet med den nationella undersökningen var att ta reda på hur Sveriges befolkning mår och lever och även att följa upp den nya folkhälsopolitiken. Syftet med urvalet för Västra Götalands län var att ta reda på hur befolkningen i Västra Götalands län mår och lever.
Hälsa på lika villkor? - Västra Götaland, 2004 - Hälsa på lika villkor, Västra Götaland - 2004
Keywords: Health Services; Hälso- och sjukvård; Physical Examination; Hälsokontroll; Body Constitution; Kroppskonstitution; Dental Care; Tandvård; Hearing; Hörsel; Life Style; Livsstil; Medicine; Medicin; Exercise; Träning; Population Surveillance; Populationsövervakning; Hearing Loss; Hörselnedsättning; Socioeconomic Factors; Socioekonomiska faktorer; Tinnitus; Öronsusning; Urinary Incontinence; Urininkontinens; Anxiety; Ångest; Overweight; Övervikt; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Work; Arbete; Asthma; Astma; Diabetes Mellitus; Diabetes; Eczema; Eksem; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Headache; Huvudvärk; Health; Hälsa; Health Status; Hälsotillstånd; Hypertension; Högt blodtryck; Body Weight; Kroppsvikt; Drug Utilization; Läkemedelsförsörjning; Gastrointestinal Diseases; Mag-tarmsjukdomar; Migraine Disorders; Migränsjukdomar; Oral Health; Munhälsa; Depression; Depression; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Registries; Register; Smoking; Rökning; Disease; Sjukdom; Pain; Smärta; Tobacco, Smokeless; Rökfri tobak; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Vision, Ocular; Syn; Sleep; Sömn; Sleep Wake Disorders; Sömn- och vakenhetsstörningar; Fatigue; Trötthet; Occupations; Yrken; Occupational Exposure; Yrkesmässig exponering; Hypersensitivity; Överkänslighet